Half-souled bodies: punishing civil servants for past state atrocities - Chan, KL (2022)
This thesis investigates the principal question of whether civil servants should be punished for past state atrocities under transitional circumstances. It looks into three sub-questions to answer this principal question. First, it inquires into whether retributivism provides an application justification of punishment in transitional circumstances. By addressing challenges about the effectiveness of punishment, the standing of the punisher, and the retroactivity of punishment, it argues that expressivist retributivism offers a defeasible justification for punishing civil servants in transitional circumstances. Second, it examines how civil servants can be held complicitly responsible for state atrocities. It proposes that an individual is complicitly responsible for a collective wrongdoing if she has taken an action that carries an impermissible risk of causing the collective wrongdoing’s success, and this action expresses a culpable choice. It also argues that this principle of complicit responsibility can overcome the problem of overdetermination. Third, it investigates what valid justifications and excuses civil servants can claim to counter blame and punishment. It rejects the cog-theory justification, the superior order justification, and the excuse of absent discriminatory intent. However, it argues that non-culpable ignorance can excuse civil servants' contribution to atrocities, and their ignorance is non-culpable if they have fulfilled their respective level of epistemic obligations. Therefore, this thesis argues that any civil servants who have contributed to state atrocities and cannot appeal to any valid justification or excuse deserve to be punished. If there are no forward-looking considerations that can outweigh retributive justice in the transitional context, these civil servants should be punished.